The origins of music - Stumpf, Carl, 1848-1936.; Trippett, David (Oxford : Oxford University Press, 2012)
Carl Stumpf was one of the founding fathers of Gestalt psychology. In this volume, first published in German in 1911 he discusses the origin and forms of musical activity as well as various theories on the origin of music.
Translated from the German.
Translated and edited by David Trippett.
At foot of title: European Society for the Cognitive Sciences of Music.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Music -- Philosophy and aesthetics; Music -- Psychological aspects